2013
DOI: 10.1103/physreve.87.053008
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness of Landau-Lifshitz energy frame in relativistic dissipative hydrodynamics

Abstract: We show that the relativistic dissipative hydrodynamic equation derived from the relativistic Boltzmann equation by the renormalization-group method uniquely leads to the one in the energy frame proposed by Landau and Lifshitz, provided that the macroscopic-frame vector, which defines the local rest frame of the fluid velocity, is independent of the momenta of constituent particles, as it should. We argue that the relativistic hydrodynamic equations for viscous fluids must be defined on the energy frame if it … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…The present choice of the coordinate system leads to the relativistic hydrodynamics in the Landau-Lifshitz frame or the energy frame [56]. From now on, we suppress the variable σ.…”
Section: An Organized Perturbation Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…The present choice of the coordinate system leads to the relativistic hydrodynamics in the Landau-Lifshitz frame or the energy frame [56]. From now on, we suppress the variable σ.…”
Section: An Organized Perturbation Theorymentioning
confidence: 99%
“…It is also understood that, in the context of the reduction theory of dynamical systems [47,48], the hydrodynamical variables constitute the natural coordinates of the invariant/attractive manifold in the functional space spanned by the distribution function. Then the renormalization group equation [33,34] or envelope equation [35,36] gives the evolution equation of the hydrodynamical variables, i.e., the hydrodynamic equation, after an averaging of the distribution function [29,31,32,43,45,46]. It has been shown that the resultant second-order relativistic hydrodynamic equation is causal and stable [29][30][31][32], the microscopic expressions for the transport coefficients coincide with those obtained by Chapman-Enskog method, and those of the relaxation times are different from any other previous ones but allow physically natural interpretations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The simple method presented in this Letter is expected to be useful for the derivation of hydrodynamic equations in other systems such as relativistic systems [28,29], an-isotropic molecular systems [30], visco-elastic systems [31][32][33], dissipative particles [34], and active matter [35]. The formulation may also be developed so as to describe more complicated behavior near boundaries.…”
mentioning
confidence: 99%